Changes in pedicle pericardial fat tissue around the anastomotic site after tracheobronchoplasty - Tsukioka, Takuma; Izumi, Nobuhiro; Komatsu, Hiroaki; Inoue, Hidetoshi; Matsuda, Yumi; Ito, Ryuichi; Kimura, Takuya; Miki, Yukio; Nishiyama, Noritoshi (Surgery today (Tokyo, Japan), 2022)
Purpose Pericardial fat is appropriate tissue to cover the bronchial anastomotic site because its harvesting is minimally invasive. We investigated the changes in pericardial fat tissue around the anastomotic site after pulmonary resection with tracheobronchoplasty. Methods The subjects of this study were 43 lung cancer patients who underwent pulmonary resection with tracheobronchoplasty. We measured the maximum cross-sectional area and average computed tomography (CT) values of the pedicle pericardial fat pad around the anastomotic site 1 week and then 6 months after the operation. Results The average volume of the residual pedicle pericardial fat pad 6 months postoperatively was 61%. A body mass index (BMI) < 21.2 kg/m 2 ( P = 0.031) and a blood albumin level < 3.4 g/dl ( P = 0.005) were significant predictors of pedicle flap shrinkage. Patients with fat tissue shrinkage had significantly elevated CT values 6 months postoperatively ( P = 0.029), whereas those without shrinkage maintained low CT values. Conclusions Preoperative nutritional conditions, reflected in high BMI and blood albumin levels, correlated with a high residual pedicle pericardial fat pad. Conversely, patients with pedicle flap shrinkage had significantly increased CT values, suggesting that the fat might have taken on another form such as scar tissue.